Helping and Hurting on the TV Screen: Bounded Generalized Reciprocity and Interracial Group Expectations. Issue 5 (3rd September 2022) - Holt, Lanier F.; Ellithorpe, Morgan E.; Ewoldsen, David R.; Velez, John
ABSTRACT: Two survey studies, one with a college sample (Study 1, n = 245) and one with a national U.S. adult sample (Study 2, n = 590) examined how media messages can influence attitudes toward Black people in the U.S. A novel contribution is the role of Bounded Generalized Reciprocity, or the belief that members of an outgroup are likely to return a favor (positive), or enact retribution for a wrong (negative) as a factor in the relationship between television use and attitudes. Study 1 (college student sample) found support for a relationship between lifetime television exposure and negative attitudes, mediated by negative reciprocity beliefs. Study 2 (U.S. adult sample) found support for an ambivalence effect, where lifetime television exposure was associated with increases in both positive and negative reciprocity beliefs. This indicates that reciprocity beliefs can be cultivated similarly to other kinds of beliefs (e.g., crime frequency, mean world), and that these beliefs have downstream relationships with racial attitudes. The direction in which they are influenced by television use remains an open question, and likely depends on TV content patterns over time.